Degraded forests are more susceptible to forest fires: Some possible ecological explanations. B Kyereh, (Journal of Science and Technology, 2016)
There is a strong belief that degraded forests are more susceptible to forest fires than non-degraded ones, but this is more intuitive than scientifically proven. The present study was conducted to investigate how fuel loading and moisture content of combustible materials; two variables that influence ignition and fire impact and therefore forests' susceptibility to fire, differ in forests with different levels of degradation. The study was done in Tain II Forest, situated in the northwest part of the forest zone and adjacent to the Savanna woodland. Three forest sites compared in this experiment were categorized as slightly degraded, moderately degraded and heavily degraded. Fuel loading was determined using the planar transect method (Brown 1974). Sampling was done on forty 200m long line transects laid in each forest site. To determine fuel and soil moisture content, wood particles and soil were monitored for changes in moisture content from November to February in the main dry season using the oven dry method. The overall pattern showed significant increases in fuel loading in more degraded forest sites. The fuel moisture content decreased from less degraded sites to heavily degraded sites for all types of fuel. The moisture content of soil sampled from the first 5cm depth was significantly lower in more degraded sites. Below 5cm depth, however the differences were not significant. These observations may explain why degraded forests have a higher likelihood of ignition and severer levels of fire damage once there is fire.